2021
DOI: 10.3389/fvets.2020.605259
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Approach to Molecular Identification of Rumen Fluke Species Across Hosts, Continents, and Sample Types

Abstract: Rumen fluke are parasitic trematodes that affect domestic and wild ruminants across a wide range of countries and habitats. There are 6 major genera of rumen fluke and over 70 recognized species. Accurate species identification is important to investigate the epidemiology, pathophysiology and economic impact of rumen fluke species but paramphistomes are morphologically plastic, which has resulted in numerous instances of misclassification. Here, we present a universal approach to molecular identification of ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
(29 reference statements)
1
18
0
Order By: Relevance
“…Trematodes of the family Paramphistomidae, known under the common name rumen fluke, are small pink pear-shaped concave amphistome flukes with two suckers, that infect a broad range of mammalian hosts including cattle, zebu, water buffalo, sheep, goats, deer and also llama and alpaca, and might have a significant impact on livestock productivity (Eduardo, 1983; Deplazes et al ., 2016; Mitchell et al ., 2021). Even though adult rumen flukes are usually well tolerated (Taylor et al ., 2007), heavy infestation with the immature flukes can result in illness associated with the intestinal phase of the infection, usually termed acute larval paramphistomosis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Trematodes of the family Paramphistomidae, known under the common name rumen fluke, are small pink pear-shaped concave amphistome flukes with two suckers, that infect a broad range of mammalian hosts including cattle, zebu, water buffalo, sheep, goats, deer and also llama and alpaca, and might have a significant impact on livestock productivity (Eduardo, 1983; Deplazes et al ., 2016; Mitchell et al ., 2021). Even though adult rumen flukes are usually well tolerated (Taylor et al ., 2007), heavy infestation with the immature flukes can result in illness associated with the intestinal phase of the infection, usually termed acute larval paramphistomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Paramphistomids have a complex life cycle involving aquatic or mud snails as intermediate hosts producing cercariae (Tilling, 2013; Horák et al ., 2019; Mitchell et al ., 2021). Ruminants become infected by ingestion of metacercariae attached to grass while grazing or the floating metacercariae may be swallowed while drinking (Rondelaud et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, species identity and taxonomy of the paramphistomes encountered in the infection of ruminants, intermediate Section Editor: Georg von Samson-Himmelstjerna host specificity and life cycle, have been a matter of intense debate in the 1970s and early 1980s and resulted in several instances in confusion, misidentification, and generation of synonyms (Odening and Gräfner 1979;Sey 1980Sey , 1982Odening 1983). However, work over the past 15 years has shown that these problems can be addressed using molecular identification methods (Mitchell et al 2021).…”
Section: Introductionmentioning
confidence: 99%